Adsorption Effect of the Modified Chitosan-Methionine Beads on Human Serum Lipids Profile and Total Protein - Ahmed Saleh (Journal of Global Pharma Technology, 2018)
This research is concerned with one of the most important applications of surface chemistry which used in medical, physical and biochemistry.Place of conducting the research University, Faculty and Department. The research is based on the adsorption of lipid profile and total protein from human serum on the surface of  modified chitosan- methionine which are associated with two different types of cross linkers substances: glutaraldehyde with two different concentration (3.13,6.25%) to prepared beads type (A,B) respectively, and ethylene glycol diglycidylether (EGDE) to prepared beads type (C). The formed beads were characterized by using Infrared (IR) spectroscopy to confirm the cross linking reaction and using Scanning Electron Microscopy (SEM) to describe the surface of the beads that used in this research. UV-Vis spectrophotometer was used to determine the concentration of the adsorbents before and after the treatment. As for adsorption of lipid profile (total cholesterol (TC), triglyceride (TG), low density lipoprotein (LDL-C) and total protein (TP)), it was observed that the adsorption of adsorbents on prepared beads type(A,B and C) followed the order (type C > type A > type B), while in case of  (high density lipoprotein (HDL-C)) , it does not adsorbed or adsorbed very little in some cases on the surface of prepared beads. Keywords: Adsorption, Adsorbent, Chitosan, Methionine, Glutaraldehyde, Ethylene glycol diglycidyl ether, Lipid profile and total protein.